Metastatic Granulosa Cell Tumor of the Testis: Clinical Presentation and Management - Anand Mohapatra; Aaron M. Potretzke; Brent A. Knight; Min Han; Robert S. Figenshau (Case Reports in Urology)
Granulosa cell tumors (GCTs) of the testis are rare sex cord-stromal tumors that are present in both juvenile and adult subtypes. While most adult GCTs are benign, those that present with distant metastases manifest a grave prognosis. Treatments for aggressive GCTs are not well established. Options that have been employed in previous cases include retroperitoneal lymph node dissection (RPLND), radiation, chemotherapy, or a combination thereof. We describe the case of a 57-year-old man who presented with a painless left testicular mass and painful gynecomastia. Serum tumor markers (alpha fetoprotein, human chorionic gonadotropin, and lactate dehydrogenase) and computed tomography of the chest and abdomen were negative. The patient underwent left radical orchiectomy. Immunohistochemical staining was consistent with a testicular GCT. He underwent a left-template laparoscopic RPLND which revealed 2/19 positive lymph nodes. Final pathological stage was IIA. He remains free of disease 32 months after surgery.